Crop wild relatives in Natura 2000 Network - Rubio Teso, Maria Luisa; Álvarez Muñiz, Clara; Gaisberger, Hannes; Kell, Shelagh; Lara-Romero, Carlos; Magos Brehm, Joana; Maxted, Nigel; Iriondo, Jose Maria (2020)
This document presents the results of analyses to ascertain the potential of the Natura 2000 network to conserve crop wild relatives (CWR). We obtained distribution data of European priority CWR from large international biodiversity databases and filtered the records to obtain a high quality georeferenced dataset. This dataset contains over 2.8 million records of 568 different priority crop wild relatives. To lay the foundation for the design of a network for the conservation of crop wild relatives in Europe, we analyzed the presence of priority taxa in the Natura 2000 network. We also consulted the Habitats Directive to identify priority crop wild relatives that are characteristic of the protected habitats under Annex I of the Directive, as well as those listed in Annexes II, IV and V.